Optimization of the return-to-sport paradigm after anterior cruciate ligament reconstruction: A critical step back to move forward - Dingenen, B.; Gokeler, A. (Sports Medicine, 2017)
Athletes who have sustained an anterior cruciate ligament (ACL) injury often opt for an ACL reconstruction (ACLR) with the goal and expectation to resume sports. Unfortunately, the proportion of athletes successfully returning to sport is relatively low, while the rate of second ACL injury has been reported to exceed 20% after clearance to return to sport, especially within younger athletic populations. Despite the development of return-to-sport guidelines over recent years, there are still more questions than answers on the most optimal return-to-sport criteria after ACLR. The primary purpose of this review was to provide a critical appraisal of the current return-to-sport criteria and decision-making processes after ACLR. Traditional return-to-sport criteria mainly focus on time after injury and impairments of the injured knee joint. The return-to-sport decision making is only made at the hypothetical `end` of the rehabilitation. We propose an optimized criterion-based multifactorial return-to-sport approach based on shared decision making within a broad biopsychosocial framework. A wide spectrum of sensorimotor and biomechanical outcomes should be assessed comprehensively, while the interactions of an individual athlete with the tasks being performed and the environment in which the tasks are executed are taken into account. A layered approach within a smooth continuum with repeated athletic evaluations throughout rehabilitation followed by a gradual periodized reintegration into sport with adequate follow-up may help to guide an individual athlete toward a successful return to sport. Abstract from author